2022
DOI: 10.7759/cureus.32616
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Action of Methanolic Petiole Extract of Eichhornia Crassipes on Human Prostate Adenocarcinoma Cell Line: An In Vitro Study

Abstract: Background: An increasing number of people are turning to herbal medicines in their search for innovative pharmaceuticals since they are effective treatments for a wide variety of conditions and traditional herbs are rich in bioactive chemicals. In this study, we looked at whether or not a petiole extract of Eichhornia crassipes preserved in methanol inhibited the proliferation of prostate cancer (PC3) cell lines.Materials and methods: Lakes in Ezhikkara, Ernakulum, Kerala, were the source of E. crassipes. Sox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We also assume the phenolic compounds which have been identified in the extract of E. crassipes contribute significantly to the reported cytotoxic activity. Previous studies have demonstrated that the phenolic compounds have antitumorigenic effects on melanoma, liver, lung, prostate, and ovarian cancer through stimulation of the nuclear factor-kappa B pathway, augmentation of genetic mutation caused by oxidative stress, or inhibition of angiogenesis [ 11 , 15 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also assume the phenolic compounds which have been identified in the extract of E. crassipes contribute significantly to the reported cytotoxic activity. Previous studies have demonstrated that the phenolic compounds have antitumorigenic effects on melanoma, liver, lung, prostate, and ovarian cancer through stimulation of the nuclear factor-kappa B pathway, augmentation of genetic mutation caused by oxidative stress, or inhibition of angiogenesis [ 11 , 15 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach, while continuous, is really only a sequence of brief macerations. We maintained room temperature while evaporating the resulting organic extracts [6].…”
Section: Eichhornia Crassipesmentioning
confidence: 99%